2006
DOI: 10.1111/j.1467-2494.2006.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Charge density alterations in human hair fibers: an investigation using electrostatic force microscopy

Abstract: A new method for high-resolution analyses of hair surface charge density under ambient conditions is presented in this paper. Electrostatic force microscopy (EFM) is used here to analyze changes in surface charge density in virgin hair, bleached hair, and hair treated with a cationic polymer. The atomic force microscopy technique is used concomitantly to analyze morphological changes in hair roughness and thickness. The EFM images depict exactly how the polymer is distributed on the surface of the hair fiber. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 8 publications
0
17
0
8
Order By: Relevance
“…Hair is considered as a dead mater and it is only alive when it is inserted in the scalp (pilose follicle). When the thread emerges, it becomes dead matter although it appears to be growing since the fiber follows increasing its length by a speed of about 1.0 cm/month (Cade, 1995;Dias, 2004;Longo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hair is considered as a dead mater and it is only alive when it is inserted in the scalp (pilose follicle). When the thread emerges, it becomes dead matter although it appears to be growing since the fiber follows increasing its length by a speed of about 1.0 cm/month (Cade, 1995;Dias, 2004;Longo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Participants reported that eyebrow bleaching was related to decreased or increased eyebrow hair density, which is most likely due to the oxidation reactions associated with bleaching. Bleaching causes chemical and electrical charge changes to the hair and its structure, which can increase or decrease the density of the hair 1,4 …”
Section: Discussionmentioning
confidence: 99%
“…Atomic Force Microscopy (AFM) enables the acquisition of a wide range of information, because it provides many imaging possibilities for different types of samples [26].…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…AFM could be applied to get certain hair strain properties, such as Particle deposition over surface and affinity to incorporated ingredients in hair care products [20,24], structural and morphological changes [26,[28][29][30][31] as well.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
See 1 more Smart Citation